Validation of optical sensors for the mDOM of the IceCube Upgrade ... - Halve, Lasse Yannik (RWTH Aachen University, 2024)
Dissertation, RWTH Aachen University, 2024; Aachen : RWTH Aachen University x, 205 Seiten : Illustrationen (2024). = Dissertation, RWTH Aachen University, 2024 ... : The IceCube Neutrino Observatory is the world’s largest neutrino telescope with 5160 optical sensors embedded in the glacial ice at the South Pole. It has discovered the flux of astrophysical neutrinos and has pinpointed three sources: Our galaxy, NGC 1068, and TXS 0506+056.In the Antarctic summer season of 2025/2026, 700 new optical modules and additional calibration and R&D devices will be deployed, forming the IceCube Upgrade. The multi-PMT Digital Optical Module (mDOM) is a newly designed, tested, and constructed module containing 24 Photomultiplier Tubes (PMTs) each. The PMTs are the central detection units of the mDOM and have to comply with strict quality criteria. This work describes the design, construction, and commissioning of a central testing facility for the PMTs. More than 10,000 PMTs needed to be tested for compliance with quality specifications. The testing facility, the testing procedures, and the results of the testing campaign are presented. A central result of the tests is that most ...